KEABSAHAN PENETAPAN STATUS TERSANGKA OLEH PENYIDIK KEPOLISIAN (STUDI PUTUSAN PRAPERADILAN NO. 39/PRA.PID/2016/PN.MDN) - Jenggel Nainggolan; Syafruddin Kalo; Mahmud Mulyadi; Edi Yunara (USU LAW JOURNAL, 2018)
ABSTRACT Determination of the suspect as a pre-trial object has been widely applied or petitioned. One of them is the determination of suspects against Syahrial Siagian on a report by Muhammad Nurdin Daulay with the Police Report no. LP/359/III/2016/RestaMedan/Sek.Medan The March 30, 2015 where in a summons to Syahrial Siagian (dated 08 April 2016 No. S-Pang/137/IV/2016/RESCRIM) as a suspect for a criminal offense against (Article 335 paragraph 1 of the Criminal Code or the Criminal Code) on Muhammad Nurdin Daulay. Reporting by Muhammad Nurdin Daulay is a form of backlash because it has been reported by Syahrial Siagian's wife Aisha Hasibuan for alleged persecution of her son Adli Dahlan Siagian and alleged defamation of Aisyah Hasibuan (wife) with police report No. LP/227/II/2016/RestaMedan/Sek.Medan The East and the police report No. LP/313/III/2016/RestaMedan/Sek.Medan The East where the above 2 (two) reporting Muhammad Nurdin Daulay has not been designated as a suspect so that the form of treatment conducted by East Sector Police Headquarters through Criminal Investigation and auxiliary investigators is an attempt to criminalize Syahrial Siagian to help Muhammad Nurdin Daulay. Efforts made by the police or not the establishment of Muhammad Nurdin Daulay as 2 (two) reporting and directly set Syahrial Siagian is a form of omission and criminalization against a person. That is, by being designated as a suspect on behalf of Syahrial Siagian then Muhammad Nurdin Daulay has bargaining value or the value of negotiations so that both the Muhammad Nurdin Daulay and Syahrial Siagian both revoke the report that included the East Medan sector policing.   Keywords: determination of suspect, pretrial, and justice